Spenser’s Popular Pastoral: Hodgepodges and Genre Trouble in The Shepheardes Calender - Abigail Shinn (Sillages Critiques)
The article explores the role played by popular culture in Edmund Spenser’s Shepheardes Calender (1579). Highlighting references to almanacs, ballads and festival culture, alongside the poem’s use of regional and colloquial language, I argue that Spenser’s distinctly English pastoral includes a commingling of classical precedent with popular motifs. The result is a cultural hodgepodge in which disparate literatures and voices combine to produce new effects, but whose constituent parts significantly remain legible to the reader. The Calender thus offers a playful, and provocative, reimagining of pastoral which advertises Spenser’s roving cultural palate and solidifies his claim to be England’s new poet.